Feasibility and reproducibility of neurochemical profile quantification in the human hippocampus at 3 T. (22nd April 2015) - Bednařík, Petr; Moheet, Amir; Deelchand, Dinesh K.; Emir, Uzay E.; Eberly, Lynn E.; Bareš, Martin; Seaquist, Elizabeth R.; Öz, Gülin
<x xml:space="preserve">Abstract</x> Hippocampal dysfunction is known to be associated with several neurological and neuropsychiatric disorders such as Alzheimer's disease, epilepsy, schizophrenia and depression; therefore, there has been significant clinical interest in studying hippocampal neurochemistry. However, the hippocampus is a challenging region to study using 1H MRS, hence the use of MRS for clinical research in this region has been limited. Our goal was therefore to investigate the feasibility of obtaining high‐quality hippocampal spectra that allow reliable quantification of a neurochemical profile and to establish inter‐session reproducibility of hippocampal MRS, including reproducibility of voxel placement, spectral quality and neurochemical concentrations. Ten healthy volunteers were scanned in two consecutive sessions using a standard clinical 3 T MR scanner. Neurochemical profiles were obtained with a short‐echo (TE = 28 ms) semi‐LASER localization sequence from a relatively small (~4 mL) voxel that covered about 62% of the hippocampal volume as calculated from segmentation of T1‐weighted images. Voxel composition was highly reproducible between sessions, with test–retest coefficients of variation (CVs) of 3.5% and 7.5% for gray and white matter volume fraction, respectively. Excellent signal‐to‐noise ratio (~54 based on the N‐acetylaspartate (NAA) methyl peak in non‐apodized spectra) and linewidths (~9 Hz for water) were achieved reproducibly in all subjects. The spectral quality allowed quantification of NAA, total choline, total creatine, myo‐inositol and glutamate with high scan–rescan reproducibility (CV ≤ 6%) and quantification precision (Cramér–Rao lower bound, CRLB < 9%). Four other metabolites, including glutathione and glucose, were quantified with scan–rescan CV below 20%. Therefore, the highly optimized, short‐echo semi‐LASER sequence together with FASTMAP shimming substantially improved the reproducibility and number of quantifiable metabolites relative to prior reports. In addition, the between‐session variation in metabolite concentrations, as well as CRLB, was lower than the between‐subject variation of the concentrations for most metabolites, indicating that the method has the sensitivity to detect inter‐individual differences in the healthy brain. Copyright © 2015 John Wiley & Sons, Ltd.